Transformational Leadership Style on Employee Performance with Employee Engagement as a Mediating Variable in a North Sumatran Pawnshop Company - Elveria Melda Sinaga; M. Chaerul Rizky; Lismayana Eryanti Siregar (Transpublika Publisher, 2025)
In the competitive financial services sector, superior employee performance is a critical determinant of organizational success. This is especially true in pawnbroking, where performance hinges on customer trust and efficient service. Transformational leadership plays a crucial role in driving performance but how exactly it impacts remains unclear. Employee engagement is believed to be the key factor that links leadership to performance outcomes. Hence, this research seeks to identify the correlation between transformational leadership demeanor and personnel efficacy, with employee engagement serving as an intervening construct at PT Budi Gadai Indonesia, Medan Branch. Adopting a quantitative paradigm, the investigation encompasses a population of 185 personnel, employing a saturated sampling technique. Data evaluation was performed through Structural Equation Modeling (SEM) predicated on Partial Least Squares (PLS) methodology via SmartPLS. The empirical findings revealed that transformational leadership style exerts a positive and influential upon employee performance (β = 0.485; p = 0.000) as well as upon work engagement (β = 0.361; p = 0.000). Moreover, work engagement has a positive and influential on employee performance (β = 0.511; p = 0.000). The mediational assessment further unveiled that work engagement significantly intermediates the nexus between transformational leadership style and employee performance (β = 0.184; p = 0.000). This research confirms that transformational leadership directly improves employee performance and work engagement, while work engagement also contributes strongly to performance improvement. In addition, work engagement is proven to be a significant mediator that bridges the influence of transformational leadership on employee performance.